MENGIDENTIFIKASI PENERAPAN KARAKTERISTIK ZAT DALAM PEMANFATANNYA DI KEHIDUPAN SEHARI-HARI - Adinda Zahra Sukmahati; Listiyana Septiyani; Giska Aryola; Wahyu Kurniawati (ScienceEdu, 2024)
This article discusses the application of substances in human daily life, the types of substances, and the changes in substances resulting from heat transfer. This research aims to provide information related to the application of substances in everyday life so that in their application and utilization they can be adapted to the needs of each individual. This article uses research methods of library studies with techniques of collecting data and information through electronic documents that can support in the writing process, examples include journals and articles. The results of the study can be concluded that in its application substances are divided into two types, namely single and mixed substances. Whereas, based on their molecular arrangement substances are divided into three namely solid, liquid, and gaseous substance. Examples of substances in everyday life are air, water, oil, tables, and rulers. Such substances can undergo a change in appearance due to changes in temperature in the surrounding environment. Substances in everyday life have benefits in every aspect of life so in their application they must be adapted to the needs so as not to have a negative impact on human life.